Urodynamic characteristics of benign prostatic hyperplasia patients complicated with chronic obstructive pulmonary disease - Chen Chaojiang, Liu Zhenfei, Zeng Xiangyu, Zheng Yu (Xin yixue, 2023)
Objective To study the urodynamic characteristics of benign prostatic hyperplasia （BPH） patients complicated with chronic obstructive pulmonary disease （COPD）. Methods Seventy-eight BPH patients were recruited and divided into the BPH complicated with COPD group （n = 43） and BPH group （n = 35）. The prostate volume and urodynamic parameters were measured between two groups. Results Compared with the BPH group， the maximum urinary flow rate was decreased， detrusor pressure at the maximum urinary flow rate was declined and the bladder contraction index （BCI） was decreased in the BPH complicated with COPD group （all P < 0.05）. There was no significant difference in age， prostate volume， residual urine volume， specific urethral resistance factor （URA）， obstruction index （OBI） pressure and bladder outlet obstruction index （BOOI） between two groups （all P > 0.05）. Conclusion BPH patients complicated with COPD show the urodynamic characteristics of detrusor underactivity of the bladder.